Assessment of the Relevance of Goleman’s Emotional Intelligence Model among the Managers of Commercial Banks in Nepal - Shrestha, Indira; Dahal, Rewan Kumar (NCC Journal, 2023)
Even if today's managers can use technology, they are accused of lacking emotional stability. However, to manage the corporate house effectively, a leader needs to possess the decisive trait of emotional stability. So, the study aimed to examine how Goleman's notion of emotional intelligence applies to bank managers. The study's participants included branch heads of commercial banks located in Kathmandu, Bhaktapur, and Lalitpur districts. Information about emotional intelligence was obtained from 215 branch heads using convenience sampling. Exploratory and confirmatory factor analyses were employed using 25 test items to confirm the constructs of emotional intelligence. Due to a low standardized regression weight, one out of 25 items could not be retained. According to the findings, self-awareness, self-regulation, motivation, empathy, and social skills are the five categories into which Nepalese bank managers fall under the emotional intelligence concept. Thus, companies can use this emotional intelligence measure to assess the characteristics of managers who constitute true leaders.